DTN Routing Algorithm Based on Perceptions of Node Mobile Information - Wang En; Yang YongJian; Chen Xi; Wu FangMing (Institute of Advanced Engineering and Science, 2013)
Due to the high mobility of nodes in DTN, the topology is changing forever. On this base, putting forward an efficient routing protocol becomes a hot topic in this area. Focus on the moving character of nodes, putting forward a routing algorithm in DTN (BMI) based on perceptions of node mobile information. This algorithm improved from the classical routing protocol spray and wait. First, change the wait phase to active routing. Then consider the moving information of meeting nodes and purpose nodes, choose a node which has a higher possibility to meet the purpose node. Simulation results show that, this algorithm can significantly improve the delivery ratio and reduce the delay. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3065